2020
DOI: 10.1158/1078-0432.ccr-19-0374
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning to Distinguish Benign from Malignant Renal Lesions Based on Routine MR Imaging

Abstract: Purpose: With increasing incidence of renal mass, it is important to make a pretreatment differentiation between benign renal mass and malignant tumor. We aimed to develop a deep learning model that distinguishes benign renal tumors from renal cell carcinoma (RCC) by applying a residual convolutional neural network (ResNet) on routine MR imaging.Experimental Design: Preoperative MR images (T2-weighted and T1-postcontrast sequences) of 1,162 renal lesions definitely diagnosed on pathology or imaging in a multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 48 publications
2
64
1
2
Order By: Relevance
“…Similarly, Xi et al developed a DL model based on MRI data and compared it to four expert radiologists to distinguish benign renal tumors from RCC. The DL model showed overall higher accuracy, sensitivity, and specificity and was comparable to expert diagnostic opinion [19]. Table 1 summarizes articles investigating the differentiation of benign from malignant lesions using radiomics strategies.…”
Section: Renal Mass Differentiationmentioning
confidence: 81%
“…Similarly, Xi et al developed a DL model based on MRI data and compared it to four expert radiologists to distinguish benign renal tumors from RCC. The DL model showed overall higher accuracy, sensitivity, and specificity and was comparable to expert diagnostic opinion [19]. Table 1 summarizes articles investigating the differentiation of benign from malignant lesions using radiomics strategies.…”
Section: Renal Mass Differentiationmentioning
confidence: 81%
“…Images were padded and resized to 512 by 512 pixels. Single-channel images were converted to 3-channel images by repeating the single channel 3 times [12,19,20]. Pixel values were normalized by scaling values into the range [0, 1], then subtracting (0485, 0456, 0406) and dividing by (0229, 0224, 0225) channel-wise.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Deep learning models can recognize predictive features directly from images by utilizing a back-propagation algorithm which recalibrates the model's internal parameters after each round of training [10]. Recent studies have shown the potential of deep learning in the assessment of solid liver lesions on ultrasonography [11], renal lesions [12,13] and glioma on MR Imaging [10,14À17] and abnormal chest radiographs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The cohort was partly overlapped with our previous work. 27 Histopathologic diagnosis was obtained for all 430 tumors after surgical excision; Fuhrman grade was available for 353 tumors according to the 4-tiered Fuhrman classification, while the other 77 tumors were graded by the 4-tiered WHO/ISUP grading system. RCCs were grouped into low-grade (grades I and II) and high-grade (grades III and IV).…”
Section: Patient Cohortmentioning
confidence: 99%